ANALYSIS OF LEGAL FRAMEWORK FOR THE IMPLEMENTATION OF AUTHORITIES OF ADVOCATE SELF-GOVERNMENT BODIES NOT LEGALLY STATUS - Артьомов, Євген Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Goal: within the scope of the research, the author identified the problematic issue of determining the legal nature of the powers of the organs of the advocate's self-government and the manner in which the powers of the Congress of Advocates of Ukraine as the highest body of lawyer's self-government in Ukraine, which forms the personal composition of other organs of the advocate's self-government, arise. The author determines that the procedure for forming the powers of the Congress of Advocates of Ukraine does not allow to assert the presence of civil-legal relations of representation between the delegates of the Congress and lawyers of Ukraine. The author came to the conclusion that the order of formation, as well as the nature of the authority of the Congress of Advocates of Ukraine, testifies to the public-law principles for the formation of his powers. Methods of research: using the dialectical method of cognition allowed to concentrate the accumulated scientific knowledge and practice of applying the law on the legal basis of the activity of the lawyer's self-government. Results: the preconditions for the low level of efficiency of the activity of the bodies of advocacy self-government are determined, and the ways of overcoming such preconditions in the modern advocacy are determined. Discussion: problems of the activity of lawyer's self-government bodies from the point of view of the norms of modern law and European integration of Ukraine.